Public perceptions of family presence during resuscitation - Dujc, Ines (Zdravstveno varstvo, 2025)
Background: In Slovenia, the practice of having family present during resuscitation (FPDR) in the clinical setting is still controversial. Therefore, the aim of the study was to explore current public perceptions regarding FPDR in Slovenia and to investigate whether demographic characteristics are related to these perceptions. Methods: A cross-sectional study was conducted using the FPDR Benefit–Risk Scale (BRS) to collect data from a sample of 618 participants. The FPDR-BRS includes 23 items rated on a 5-point Likert scale (1 = strongly disagree to 5 = strongly agree). The online survey was conducted from 15 September to 30 December 2023. Inferential statistics were computed using IBM SPSS version 25. Results: The results indicate moderately favourable attitudes towards FPDR among participants in general. Older individuals (aged 60–82) and respondents not affiliated with the healthcare sector scored higher on the overall FPDR-BRS, indicating more favourable attitudes towards the practice of FPDR. Respondents who had previous experience with cardiopulmonary resuscitation were less concerned that FPDR could cause psychological trauma to family members. Conclusions: These findings have significant implications for the adoption of FPDR policies and practices in the healthcare sector. Healthcare providers should prioritise education, training and support as the presence of family members during resuscitation becomes more widely accepted.
Keywords: cardiopulmonary resuscitation; family-centred care; family-witnessed resuscitation; javno mnenje; kardiopulmonalno oživljanje; kvantitativna študija; oskrba osredotočena na družino; oživljanje v prisotnosti družinskih članov; percepcija; perception; public opinion; quantitative study